2004
DOI: 10.1016/j.ydbio.2004.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-promoted cyclin B1 degradation in mouse oocytes requires the establishment of a metaphase arrest

Abstract: CDK1-cyclin B1 is a universal cell cycle kinase required for mitotic/meiotic cell cycle entry and its activity needs to decline for mitotic/meiotic exit. During their maturation, mouse oocytes proceed through meiosis I and arrest at second meiotic metaphase with high CDK1-cyclin B1 activity. Meiotic arrest is achieved by the action of a cytostatic factor (CSF), which reduces cyclin B1 degradation. Meiotic arrest is broken by a Ca2+ signal from the sperm that accelerates it. Here we visualised degradation of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 80 publications
2
45
0
Order By: Relevance
“…Three different cell cycle resumption endpoints were assessed, as was done previously (Ducibella et al 2002): (1) metaphase II arrest, (2) full progression to embryonic interphase, and (3) metaphase III which is an intermediate state in which the egg completes meiosis but does not continue to embryonic interphase (as a result of M-phase promoting factor (MPF) activity decreasing only transiently, due to insufficient [Ca 2C ] cyt increases, and then returning to high levels (Kubiak 1989, Ducibella et al 2002, Hyslop et al 2004). As the post-fertilization Ca 2C transients were increasingly attenuated, the proportion of eggs exiting metaphase II arrest gradually decreased, while the proportion of eggs remaining arrested at metaphase II increased (Supplementary Figure 1, which can be viewed online at http:// www.reproduction-online.org/supplemental/).…”
Section: Resultsmentioning
confidence: 99%
“…Three different cell cycle resumption endpoints were assessed, as was done previously (Ducibella et al 2002): (1) metaphase II arrest, (2) full progression to embryonic interphase, and (3) metaphase III which is an intermediate state in which the egg completes meiosis but does not continue to embryonic interphase (as a result of M-phase promoting factor (MPF) activity decreasing only transiently, due to insufficient [Ca 2C ] cyt increases, and then returning to high levels (Kubiak 1989, Ducibella et al 2002, Hyslop et al 2004). As the post-fertilization Ca 2C transients were increasingly attenuated, the proportion of eggs exiting metaphase II arrest gradually decreased, while the proportion of eggs remaining arrested at metaphase II increased (Supplementary Figure 1, which can be viewed online at http:// www.reproduction-online.org/supplemental/).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that [Ca 2+ ] i mediates the degradation of cyclin B1 by increasing the activity of an E3 ubiquitin ligase (29,30). Cyclin B1 is the regulatory subunit of M-phase promoting factor and its destruction is required for meiosis resumption (31,32 2+ ] i oscillations, was optimal for oocyte activation, and exhibited a better development than 1-and 2-h treatment, possibly reflecting the toxic effects of prolonged [Ca 2+ ] i oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…These sperminduced Ca 2C oscillations release the egg from meiotic arrest by targeting cyclin B for destruction by the proteosome (Hyslop et al 2004). Similar to meiotic resumption, the Ca 2C increase at fertilisation is responsible for triggering cortical granule exocytosis and pronuclear formation.…”
Section: Introductionmentioning
confidence: 98%